Single-cell transcriptome and cell-specific network analysis reveal the reparative effect of neurotrophin-4 in preantral follicles grown in vitro - Yingchun Guo; Peigen Chen; Tingting Li; Lei Jia; Yi Zhou; Jiana Huang; Xiaoyan Liang; Chuanchuan Zhou; Cong Fang (BMC, 2021)
Abstract Background In-vitro-grow (IVG) of preantral follicles is essential for female fertility preservation, while practical approach for improvement is far from being explored. Studies have indicated that neurotrophin-4 (NT-4) is preferentially expressed in human preantral follicles and may be crucial to preantral follicle growth. Methods We observed the location and expression of Tropomyosin-related kinase B (TRKB) in human and mouse ovaries with immunofluorescence and Western blot, and the relation between oocyte maturation and NT-4 level in follicular fluid (FF). Mice model was applied to investigate the effect of NT-4 on preantral follicle IVG. Single-cell RNA sequencing of oocyte combined with cell-specific network analysis was conducted to uncover the underlying mechanism of effect. Results We reported the dynamic location of TRKB in human and mouse ovaries, and a positive relationship between human oocyte maturation and NT-4 level in FF. Improving effect of NT-4 was observed on mice preantral follicle IVG, including follicle development and oocyte maturation. Transcriptome analysis showed that the reparative effect of NT-4 on oocyte maturation might be mediated by regulation of PI3K-Akt signaling and subsequent organization of F-actin. Suppression of advanced stimulated complement system in granulosa cells might contribute to the improvement. Cell-specific network analysis revealed NT-4 may recover the inflammation damage induced by abnormal lipid metabolism in IVG. Conclusions Our data suggest that NT-4 is involved in ovarian physiology and may improve the efficiency of preantral follicle IVG for fertility preservation.